A forensic population database in El Salvador: 58 STRs and 94 SNPs. (March 2022) - Casals, Ferran; Rasal, Raquel; Anglada, Roger; Tormo, Marc; Bonet, Núria; Rivas, Nury; Vásquez, Patricia; Calafell, Francesc
Abstract: We have genotyped the 58 STRs (27 autosomal, 24 Y-STRs and 7 X-STRs) and 94 autosomal SNPs in Illumina ForenSeq™ Primer Mix A in a sample of 248 men and 143 women from El Salvador, Central America. Regional division (Centro, Oriente, Occidente) showed in almost all cases F ST values not significantly different from 0, and further analyses were applied only to the undivided, country-wide population. The overall random match probability (RMP) decreased from 6.79 × 10 −31 in length-based genotypes in the 27 autosomal STRs to 1.47 × 10 −34 in repeat-sequence based genotypes. Combining the autosomal loci in this set, RMP reaches 2.97 × 10 −70 . In a population genetic analysis, El Salvador showed the lowest F ST values with US Hispanics both for autosomal and X-STRs; however, it was much closer to Native Americans for the latter than for the former, in accordance with the well-known gender-biased admixture that created most Latin American populations. Highlights: Genotyped 58 STRs (27 autosomal, 24 Y-STRs and 7 X-STRs) and 94 autosomal SNPs. Samples from the general population of El Salvador (ES, Central America). Used Verogen ForenSeq™ Primer Mix A to generate length and repeat-sequence alleles. Extremely low overall RMP means it can be applied successfully even if many loci fail. Could be used to identify missing people from ES civil war and deceased migrants.